A Juridical Analysis Using a Forensic Linguistics Approach on WhatsApp Conversations in the Case of Alleged Obstruction of Justice - Aisyah Nisrina Ayu Sugiharto; Erpuat Erpuat (International Journal Labs, 2025)
This study aims to examine the alleged obstruction of justice communicated through conversations on the WhatsApp messaging application. The subject of this research is the alleged criminal act of obstruction of justice committed by the Secretary General of the Indonesian Democratic Party of Struggle (PDI-P), Hasto Kristiyanto (HK), who is suspected of attempting to hinder the investigation conducted by the Corruption Eradication Commission (KPK) in relation to a bribery case involving the interim replacement (PAW) of a member of the Indonesian House of Representatives, identified by the initials HM. The alleged obstruction of justice was conveyed via WhatsApp messages, which reportedly contained instructions from the accused (HK) to one of his staff members, identified as witness K, to dispose of the mobile phone used during the relevant period to prevent it from being seized[A1] by KPK investigators. This research adopts a juridical analysis method using a descriptive qualitative approach, combined with forensic linguistics through pragmatic analysis, specifically speech act theory and conversational implicature. This framework is employed to analyze digital conversations as evidence in proving the criminal act of obstruction of justice. The findings indicate the use of directive illocutionary acts in the phrases